Plan de mejoramiento continuo de la calidad bajo el enfoque de la Norma ISO 9001:2015 para la empresa PASTOLAC. - Aguaiza Iza, Andrea Natali (2019)
The continuous improvement plan consists on actions programmed to achieve an increase in the quality and performance of the results of an organization focused mainly on the chronic problems that it has. The main objective of this project was to develop a continuous quality improvement plan for the company PASTOLAC, where the level of maturity of quality was determined by applying the detailed evaluation to determine the level of maturity of a company established by the standard. ISO9004: 2000 as a result the value of 1.32 was obtained which establishes that the company has a poor-quality maturity level since it has poor or unpredictable results. The Audit Check ISO9001: 2015 was also applied where the current situation of the company could be visualized thus determining the non-conformities existing in it. A process map was made in order to classify the non-conformities in the improvement plan by processes. The improvement plan was drawn up based on the non-conformities found, improvement actions were determined for each of them, each action was prioritized to determine the order of execution in the plan. This is classified by strategic, key and support processes. The plan contains actions for improvement, as well as responsible for the action, assigned resources, calendar, indicators and responsible for monitoring each of them. The plan also has a Gantt chart where the total execution time for all improvement actions was established. This plan determined proposals for improvement actions that with their correct implementation strengthen the weak points and at the same time allow to have a look towards the quality certification for the company PASTOLAC.